KLASIFIKASI EMOSI PADA TOKOH UTAMA IRHAM DALAM NOVEL PROELIUM KARYA FEBRIALDI R (KAJIAN PSIKOLOGI SASTRA) - Axel Athaullah; Wahyu Wibowo; Sukirno Sukirno (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research will analyze the classification of emotions experienced by the main character, Irham in the novel Proelium by Febrialdi R. The theory used in this research is David Kreech's theory of emotional classification. Then the method used is descriptive qualitative, which produces data in the form of written words in the novel. This research examines four forms of emotion: Basic emotions, emotions related to sensory stimulation, emotions related to self-evaluation, and emotions related to other people. The results of this research show that the main character Irham experiences various emotions such as happiness, anger, fear, sadness, disgust, enjoyment, success, failure, sadness, shame, guilt, regret, love and hate. This research will enrich our understanding of the complexity of human emotions expressed through literary works, especially in the novel Proelium by Febrialdi R.